The Development of King Saud University in the Twentieth Century: (A historical perspective) - Dr. Saud Ghassan Albeshir; Dr. Areej Makki Aljahani (Journal of Arts, Literature, Humanities and Social Sciences, 2025)
The current study aims to explore the most important events that led to the development of King Saud University in the twentieth century. The study used a historical approach, as appropriate to the objectives and research question. The most important findings are as follows: King Saud University was founded in 1957 as the first modern university in the Kingdom. Its name was changed to "University of Riyadh" in 1964, before being renamed "King Saud University" in 1982. In its early years, the Egyptian scholar Dr. Abdul Wahab Azzam assumed the position of the university’s first president. In the same year, the College of Arts was established as the first college, comprising four departments: Arabic Language, English Language, History, and Geography. The initial nucleus of the faculty consisted primarily of non-Saudi professors from sister Arab countries, given the recent university experience and the scarcity of qualified national talent at the time. The first four years of study were limited to male students, followed by female students in higher education in 1961. The university has welcomed international students since its first year. The first accepted class in 1957 included three international students compared to eighteen local students. As the academic structure consolidated and the colleges expanded, graduate programs began in the early 1970s, ushering in a new phase of academic and research development that strengthened the university’s standing at the national and regional levels.